Genome of the human hookworm Necator americanus - Tang, Yat T. (2014)
The hookworm Necator americanus is the predominant soil-transmitted human parasite. Adult worms feed on blood in the small intestine, causing iron deficiency anaemia, malnutrition, growth and development stunting in children, and severe morbidity and mortality during pregnancy in women. Characterization of the first hookworm genome sequence (244 Mb, 19,151 genes) identified genes orchestrating the hookworm's invasion of the human host, genes involved in blood feeding and development, and genes encoding proteins that represent new potential drug targets against hookworms. N. americanus has undergone a considerable and unique expansion of immunomodulator proteins, some of which we highlight as potential novel treatments against inflammatory diseases. We also utilize a protein microarray to demonstrate a post-genomic application of the hookworm genome sequence. This genome provides an invaluable resource to boost ongoing efforts towards fundamental and applied post-genomic research, including the development of new methods to control hookworm and human immunological diseases.